Investigation of the Molecular Mechanisms by Which Endothelin-3 Stimulates Preadipocyte Growth - Siao, An-Ci; Shih, Li-Jane; Lin, Yen-Yue; Tsuei, Yi-Wei; Kuo, Yow-Chii; Ku, Hui-Chen; Chuu, Chih-Ping; Hsiao, Po-Jen; Kao, Yung-Hsi (Frontiers in Endocrinology, 2021)
Endothelins induce many biological responses, and they are composed of three peptides: ET-1, ET-2, and ET-3. Reports have indicated that ET-1 regulates cell proliferation, adipogenesis, and other cell responses and that ET-3 stimulates the growth of gastrointestinal epithelial cells and melanocytes. However, the signalling pathways of ET3 that mediate the growth of fat cells are still unclear. Using 3T3-L1 white preadipocytes, we found that ET-3 induced increases in both cell number and BrdU incorporation. Pretreatment with an ETAR antagonist (but not an ETBR antagonist) blocked the ET-3-induced increases in both cell number and BrdU incorporation. Additionally, BQ610 suppressed the ET-3-induced increases in phosphorylation of AMPK, c-JUN, and STAT3 proteins, and pretreatment with specific inhibitors of AMPK, JNK/c-JUN, or JAK/STAT3 prevented the ET-3-induced increases in phosphorylation of AMPK, c-JUN, and STAT3, respectively. Neither p38 MAPK inhibitor nor PKC inhibitor altered the effects of ET-3 on cell growth. These data suggest that ET-3 stimulates preadipocyte growth through the ETAR, AMPK, JNK/c-JUN, and STAT3 pathways. Moreover, ET-3 did not alter HIB1B brown preadipocyte and D12 beige preadipocyte growth, suggesting a preadipocyte type-dependent effect. The results of this study may help explain how endothelin mediates fat cell activity and fat cell-associated diseases.